2020
DOI: 10.1007/s00192-020-04253-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in a fitness club setting—is it a workout problem?

Abstract: Introduction The aims of the present study were to report longitudinal data on the prevalence of urinary incontinence (UI) in a fitness club setting and to investigate whether gym members are educated about and exercise their pelvic floor muscles. Methods New members (125 women) from 25 fitness clubs in Oslo, Norway, filled in a 25-min online questionnaire (SurveyXact) at four time points (onset, 3, 6 and 12 months of fitness club membership). The questionnaire covered background/health information, membership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
0
17
1
1
Order By: Relevance
“…Most of studies on PFMT have observed the effect of PFMT on improving the QOL of women with urinary incontinence complaints. Different things were found in research by Haakstad et al (2020), which found that adherence to PFMT for 12 months did not show a correlation with urinary incontinence, including the QOL.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…Most of studies on PFMT have observed the effect of PFMT on improving the QOL of women with urinary incontinence complaints. Different things were found in research by Haakstad et al (2020), which found that adherence to PFMT for 12 months did not show a correlation with urinary incontinence, including the QOL.…”
contrasting
confidence: 54%
“…In previous studies, yoga interventions were carried out at varying times between 20-40 minutes per day at home and 70-90 minutes under instructor supervision for 8-18 weeks (Jayabharathi & Judie, 2014;Kim et al, 2015;Reed et al, 2014). Meanwhile, PFMT is carried out for 30-40 minutes for 8-12 weeks (Fitz et al, 2017;Haakstad et al, 2020;Kim et al, 2015;Liu et al, 2018). PFMT could be done at any time without providing a specific time; it could be done in a short time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Neels et al [29] reported that only 7.1% of pregnant women had received information about the PFM before pregnancy, e.g., during yoga or Pilates classes, back school, or sporting activities. This confers with a recent study among new members from 25 fitness clubs in Oslo, Norway, in which less than 8% had received any information about PFMT by the fitness club staff [21]. If the instructors learn how to teach PFMT correctly, general exercise classes have the potential to become an important arena for PFMT.…”
Section: Discussionmentioning
confidence: 95%
“…Using data from the research project "Fitness clubs -a venue for public health?" (Gjestvang et al, 2017(Gjestvang et al, , 2019(Gjestvang et al, , 2020aHaakstad et al, 2020;Heiestad et al, 2020), we aimed to investigate different psychosocial factors that might increase the likelihood of reporting regular exercise the first year of a fitness club membership, including self-efficacy, social support, motives, life satisfaction, and customer satisfaction. Our hypothesis was that self-efficacy, perceived motives considered as intrinsic, and social support would be higher in regular exercisers compared with those reporting non-regular exercise attendance.…”
Section: Introductionmentioning
confidence: 99%